Kinesioterapia en la atención a niños menores de 5 años con retraso del desarrollo psicomotor - Jiménez Maldonado, Pamela Soledad (2020)
Through the investigation of kinesitherapy in the care of children under 5 years of age with delayed psychomotor development, it was found the need to analyze the effects produced by kinesitherapy when attending to children with this pathology. Psychomotor development includes ah all those skills that the child is continuously acquiring throughout his childhood, also to the maturation of nervous structures such as the brain, spinal cord, nerves and muscles; as to the learning that the child is discovering himself and the world around him. Psychomotor retardation includes the behaviors or physical skills of development; that children must acquire within a certain age, it is required to specify if these are anomalous. The Bobath method as a treatment aid since through this we inhibit abnormal tone and movement patterns, facilitating normal movement and stimulating in cases of hypotonia or muscular inactivity. Within this study, early Stimulation has been used to provide the baby with a greater physical and intellectual development so that his abilities and abilities allow him to be better than he would have been stimulated naturally. The literature review was based on the investigation of various studies with scientific contribution that refer to kinesitherapy in the care of children under 5 years of age with psychomotor retardation, the methodology applied includes the method of observation. The approach is qualitative because it allowed us to know the characteristics that are presented in a child with psychomotor and quantitative delay because there were 35 studies selected according to the PEDro assessment scale, the same ones that were participants in the present investigation. The selected population corresponds to 35 documents in which they refer to the application of kinesitherapy in children under 5 years of age with psychomotor disorder, which were found in databases such as PubMed, Elsevier, Scielo, Google scholar, Proquest were validated by PEDro's scale. The different documents agree that when applying kinesitherapy as an intervention method during physiotherapeutic treatment, it significantly favored the development of their sensory, motor, cognitive and better quality of life.